Using transcriptomics to enable a plethodontid salamander (Bolitoglossa ramosi) for limb regeneration research (2018)
ABSTRACT: Background: Tissue regeneration is widely distributed across the tree of life. Among vertebrates, salamanders possess an exceptional ability to regenerate amputated limbs and other complex structures. Thus far, molecular insights about limb regeneration have come from a relatively limited number of species from two closely related salamander families. To gain a broader perspective on the molecular basis of limb regeneration and enhance the molecular toolkit of an emerging plethodontid salamander (Bolitoglossa ramosi), we used RNA-Seq to generate a de novo reference transcriptome and identify differentially expressed genes during limb regeneration. Results: Using paired-end Illumina sequencing technology and Trinity assembly, a total of 433,809 transcripts were recovered and we obtained functional annotation for 142,926 non-redundant transcripts of the B. ramosi de novo reference transcriptome. Among the annotated transcripts, 602 genes were identified as differentially expressed during limb regeneration. This list was further processed to identify a core set of genes that exhibit conserved expression changes between B. ramosi and the Mexican axolotl (Ambystoma mexicanum), and presumably their common ancestor from approximately 180 million years ago. Conclusions: We identified genes from B. ramosi that are differentially expressed during limb regeneration, including multiple conserved protein-coding genes and possible putative species-specific genes. Comparative analyses reveal a subset of genes that show similar patterns of expression with ambystomatid species, which highlights the importance of developing comparative gene expression data for studies of limb regeneration among salamanders.